Innovation Off the Bat: Bridging the ChatGPT Gap in Digital Competence among English as a Foreign Language Teachers - Gulsara Urazbayeva; Raisa Kussainova; Aikumis Aibergen; Assel Kaliyeva; Gulnur Kantayeva (MDPI AG, 2024)
This research explores the guided experimental implementation of ChatGPT as a tool for developing teachers' skills in teaching English. The intervention involved 24 in-service English as a Foreign Language (EFL) teachers who engaged in crafting activities and assessments using researcher-designed prompts. Utilizing a mixed-methods approach, the researchers assessed the participants' ChatGPT integration proficiency through a custom-designed assessment tool aligned with the technological pedagogical content knowledge framework. The eight-week intervention introduced educators to various applications of ChatGPT in EFL teaching, including lesson planning. A quantitative analysis revealed statistically significant improvements in the teachers' ChatGPT integration proficiency across all measured dimensions. The qualitative findings highlight the perceived benefits, challenges, and future prospects of ChatGPT in EFL education. While the practical significance of the improvement was modest, the results suggest that the guided integration of generative chatbots can bolster teachers' ability to leverage this technology appropriately. This study contributes to the limited body of empirical research on integrating large language models into teaching and offers insights into the practical applications and challenges of using ChatGPT in EFL contexts.